Hubungan Antara Job Demand Dengan Father Involvement Pada Ayah Yang Bekerja Sebagai Petugas Pemadam Kebakaran Di Padang Panjang - Ketut Lativa Chairunnisa; Zulian Fikry (Science and Education Journal (SICEDU), 2026)
This study aims to examine the relationship between job demand and father involvement among fathers working as firefighters in Padang Panjang. The issue of low father involvement in parenting remains a significant concern, particularly in occupations with high work demands. This research employed a quantitative approach with a descriptive correlational design. The participants consisted of 29 fathers selected using a total sampling technique. Data were collected using the Inventory of Father Involvement (IFI) and the Questionnaire for the Experience and Evaluation of Work (QEEW 2.0). Data analysis was conducted using simple linear regression with the assistance of JASP software. The results showed that most participants had moderate levels of job demand and father involvement. Furthermore, there was a significant negative relationship between job demand and father involvement (p < 0.05; β = -0.722). This indicates that higher job demand is associated with lower father involvement in parenting. Job demand contributed 52.1% to father involvement.